2019
DOI: 10.1186/s13018-019-1340-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and patient-reported outcomes of three procedures for recurrent anterior shoulder instability: arthroscopic Bankart repair, capsular shift, and open Latarjet

Abstract: Background Best surgical of recurrent anterior shoulder instability remained controversial. We knew little about the superiority and choice between traditional open and modern arthroscopic techniques. We hypothesized that outcomes of all patients will be similar regardless of surgical technique. Methods A retrospective case-cohort analysis of 168 patients who had recurrent anterior shoulder instability was conducted from September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Our result showed that the open Latarjet procedure to produce better patient-reported outcomes compared to the arthroscopic Bankart procedure, and the external rotation was also not reduced in the Latarjet group. Our results add to the literature that the Latarjet procedure is a viable option with satisfactory clinical and functional outcomes [12,33,18,17,6].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Our result showed that the open Latarjet procedure to produce better patient-reported outcomes compared to the arthroscopic Bankart procedure, and the external rotation was also not reduced in the Latarjet group. Our results add to the literature that the Latarjet procedure is a viable option with satisfactory clinical and functional outcomes [12,33,18,17,6].…”
Section: Discussionsupporting
confidence: 66%
“…Patient-reported outcomes, following surgical stabilization procedure, are solely dependent upon the postoperative function, pain, and recurrence [6,17,18]. These factors also determine the functional satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although conservative treatment and open surgery have been the main treatment methods for these diseases, with the popularization of arthroscopy technology, it has become one of the main treatment option [5,6]. The main application advantages of shoulder arthroscopy are less injury of shoulder joint, su cient removal of focus, low postoperative pain and fast recovery [7]. It is estimated that more than 270,000 patients underwent rotator cuff repair in 2006 in the United States and more than 250,000 patients completed rotator cuff repair under shoulder arthroscopy [8].…”
Section: Introductionmentioning
confidence: 99%